Utilization of residual soil from landslide as an absorbing material in the production of anti-microwave bricks / Nur Hashira Narudin … [et al.] - Narudin, Nur Hashira; Abdullah, Hasnain; Taib, Mohd Nasir; Abdul Hadi, Basharudin; Ahmad, Azizah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
Wireless technology plays a key role in today’s communications and has become a crucial component in our daily life and brings a lot of positive effects such as; increased mobility, better communication, improved productivity, and allow access to real-time information. However, excessive usage of this technology has increased electromagnetic pollution which poses negative effects on electronic devices and human health. Therefore, to solve this problem, it is important to develop electromagnetic absorbers or anti-microwave materials. In this study, bricks were designed and fabricated as innovative anti-microwave bricks. Brick is a basic and the most used construction material all over the world and cement is the most important raw material for its production. For the innovative anti-microwave bricks, residual soil from landslide was used as partial cement replacement. The objective of this study is to investigate the residual soil as a radiation absorbing material in the production of innovative anti-microwave bricks. Residual soils are widely used as a construction material since it is easily available and economical. NRL Arch free space method was used to determining the absorption performance of the innovative anti-microwave bricks in the frequency range between 1 to 12GHz, at three different angles which are; 0⁰, 30⁰, and 60⁰. The absorption performance of the bricks is shown in the graph of absorption (dB) versus frequency (GHz). The measurement result shows that the maximum absorption of the innovative anti-microwave bricks is -22.45dB at a frequency 2.4GHz. This can be concluded that the residual soil from landslides can be used as a radiation absorbing material.